An organic photovoltaic featuring graphene nanoribbons1. Issue 44 (4th June 2015) - Lee, Seung Joo; Kim, Jae-Yeon; Kim, Hyeong Pil; Kim, Dongcheon; da Silva, Wilson Jose; Schneider, Fabio Kurt; Mohd Yusoff, Abd. Rashid bin; Jang, Jin
<x xml:space="preserve">Abstract</x> A combination of graphene nanoribbons (GNRs) and carbon nanotubes (CNTs) was deployed as a potential candidate to replace the commonly used hole transport material poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) in a high performance organic photovoltaic.